Biological Activities of Some Derivatives of Pyrimidine, Oxadiazole and Indole in Combination - Muthumani, P (International Journal of Pharmaceutical & Biological Archive, 2010)
The derivatives of pyrimidine, oxadiazole and indole in combination compounds were synthesized by Conventional method and Micro wave method .The antimicrobial activity of the synthesized compounds were evaluated on S.aureus , B.subtilis, E.coli and P.aeroginosa. The anti oxidant activity was determined by DPPH assay method. The present investigation deals with the synthesized compounds possessing good antioxidant and antibacterial activity.